An Interdisciplinary Model to Foster Existential Resilience and Transformation - Ingela Steij Stålbrand; Ive Brissman; Lovisa Nyman; Erik Sidenvall; Mattias Tranberg; Anika Wallin; Christine Wamsler; Juliet Jacobsen (Challenges)
Existential threats, including threats to the self, society, and the planet, are present throughout the lifespan and form a core element of the human experience. To consolidate knowledge and constructs about how people can adequately respond to existential threats, we convened an interdisciplinary working group, which consisted of eight researchers from the fields of psychology, systemic theology, practical theology, religious studies, cognitive science, palliative care, and sustainability science. The group met one day per week for 9 months to engage in an interactive co-creative process of data collection and analyses, discussion, iterative presentations, and writing. The process resulted in the development of an interdisciplinary model that pulls together the key themes of how people, societies, and systems can foster existential resilience and transformation. The model consists of three axes across which we (individuals, groups, systems) have to strengthen or stretch our “inner muscles”: connectedness, agency, and time. All axes contribute to the development of our inner capacities and, ultimately, meaning and purpose, which are crucial to support resilience and transformation. Our interdisciplinary overarching model provides a common conceptualization for existential resilience and transformation that can bridge existing research to support individual, collective, and large-scale system-change work. Its relevance and potential implementation are illustrated and presented from different disciplinary angles.